AN INVESTIGATION OF SMARTPHONE ADDICTION AND ITS PERCEIVED EFFECTS ON SLEEP-PATTERN AND ACADEMIC PERFORMANCE AMONG STUDENTS AT SCHOOL OF NURSING IN NORTH CENTRAL NIGERIA - Bamidele, Feyisayo Iyabo; Anyebe, Emmanuel Ejembi; Omoniyi, Sunday Oluwafemi; Yakubu, Monsurat Oyenike; Akapo, Bolanle Oluwaseun; Sanni, A. O. (FUDMA JOURNAL OF SCIENCES, 2024)
The study aimed at investigating Smartphone addiction, its perceived effect on sleep pattern and academic performance on student nurses in the School Complex, University of Ilorin Teaching Hospital. A descriptive cross-sectional study design was utilized for the study. The study deployed stratified and proportionate sampling method to select students from the three levels of students. The sample size was 121 with a proportion of 41, 33, and 47 for 100L, 200L and 300L students’ nurses. A self-administered questionnaire developed by the researchers was used for data collection from the respondents and only 120 were valid for analysis, using SPSS Version 20. The findings revealed that 78% of the participants were highly addicted to their Smartphone’s; only 5% were not addicted. However, nearly half of the students indicated that they feel excessively tired and sleepy in class and agreed that their sleep pattern is altered due to excessive Smartphone usage while almost half of the participants missed planned work due to Smartphone usage. Additionally, the study revealed that, there is a significant relationship between age and the level of addiction to Smartphone among students (p< 0.04). The study thus shows a high level of Smartphone addiction among the student nurses in the setting. It is therefore, recommended that interventions and awareness programs be created to address excessive Smartphone use and promote healthier sleep habits.